2017
DOI: 10.1111/den.12862
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic capability of colon capsule endoscopy for advanced colorectal cancer: A pilot study

Abstract: The diagnostic capability of CCE in detecting advanced CRC was limited in cases of procedure incompletion. Refining procedures to increase CCE procedure completion rates are required to enhance CRC detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Six studies [13][14][15][16][17][18] had a low risk of bias in relation to patient selection, as either random or consecutive sample of patients were used. Two studies [19,20] were classified with high risk of bias in relation to the index test (CCE), as descriptions of the blinding process were insufficient. Because of the unproven capability of colonoscopy as a true gold standard, the reference standard (colonoscopy) was classified as high risk of bias in all studies but one [16], which used a segmental unblinding during the colonoscopy procedure.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies [13][14][15][16][17][18] had a low risk of bias in relation to patient selection, as either random or consecutive sample of patients were used. Two studies [19,20] were classified with high risk of bias in relation to the index test (CCE), as descriptions of the blinding process were insufficient. Because of the unproven capability of colonoscopy as a true gold standard, the reference standard (colonoscopy) was classified as high risk of bias in all studies but one [16], which used a segmental unblinding during the colonoscopy procedure.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
“…Only the study by Ota et al [20] reported sensitivity and specificity for detection of cancer. However, as all included patients were CRC positive on inclusion, only sensitivity was re-ported.…”
Section: Diagnostic Yield Of Other Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTC has high patient acceptability and high sensitivity for polypoid lesions [8,9], whereas CCE has higher sen- sitivity for non-polypoid tumours as demonstrated in the present study. Even advanced colon cancers can be missed in failed CCE studies [32], but CTC can depict advanced colon cancers in almost 100% [8,9]. The combination of CCE and CTC might be useful as a colon screening test.…”
Section: Cce Versus Ctc For Non-polypoid Tumoursmentioning
confidence: 99%
“…Recently, a minimally invasive method, colon capsule endoscopy (CCE), has been used to investigate these neoplasms [2,3]. However, it is time-consuming to review 50 000 images per patient (requiring approximately 1 hour) [4].…”
Section: Introductionmentioning
confidence: 99%